Patient-Centered Satisfaction After Secondary Correction of the Cleft Lip and Nasal Defect. (July 2020) - Rothermel, Alexis; Loloi, Justin; Long, Ross E.; Samson, Thomas
Objective: To evaluate patient-reported aesthetic and psychosocial outcomes of secondary cleft lip and nose revision procedures. Design: Single-center cohort study. Setting: Tertiary care pediatric hospital. Patients/Participants: Patients who underwent secondary revision procedures for cleft lip and nasal defect (N = 42). Interventions: Patients were administered a survey during a routine postoperative clinic visit. Main Outcome Measure(s): Outcome measures were planned prior to data collection and included improvement in appearance seen in lip and nose, satisfaction with revision procedure, changes in self-confidence, likelihood to participate in social activities, and effect on teasing by peers. Results: Patients agreed that an improvement was seen in the appearance of their lip (1.93) and nose (1.98) following surgery. Overall, patients felt satisfied with the results of their revision procedure (1.76). An improvement in confidence and decrease in feelings of self-consciousness was reported. Patients were teased less by their peers and more likely to participate in social activities. Conclusions: Secondary revision procedures of the cleft lip and nasal defect provide a patient-reported improvement in appearance and a positive psychosocial impact on patient's lives.